(untitled) (Chemical Engineering Research Bulletin, 2017)
The excretion of recombinant proteins into the culture medium is a preferred approach over cytoplasmic expression because of the high specific activity and ease of purification. However, cell lysis is one of a major problem during the excretion of recombinant protein due to the pressure build up in the periplasmic space through overproduction of the expressed recombinant protein. Cell immobilization is a promising solution for the improvement of protein excretion with reduction in cell lysis. In this study, the effect of cross linkers concentrations on the process of cell immobilization for the cyclodextringlucanotransferase (CGTase) excretion and cell viability were investigated. The hollow fiber membrane was treated using different concentrations (0.3, 0.67 and 1%) of cross linkers namely glutaraldehyde (GA), poly-L-lysine (PLL) and polyethylenimine (PEI). The optimum concentration of cross linkers was found to be 0.3% with the high excretion of CGTase. Interestingly, the immobilized cell on the non-treated hollow fiber membrane showed up to 15% increment of CGTase excretion with 55% reduction of cell lysis, as compared to the immobilized cells on the treated hollow fiber membrane. It could be concluded that, the low concentration of cross linkers exhibited the highest CGTase excretion. Moreover, the non-treated hollow fiber membrane is a promising approach for attachment of cells to the membrane without requiring treatment with any chemicals for the production of recombinant enzyme. Chemical Engineering Research Bulletin 19(2017) 154-159